Trade in services and innovation - Bastian Krieger; Fabian Trottner (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
We study the implications of services trade for firm innovation. Using a quasi-experimental shift-share design, we find that access to foreign knowledge-related services improves the innovativeness of domestic firms and complements their indigenously sourced R&D. To confront this evidence, we develop a theoretical model. It demonstrates outsourcing can foster firms' innovation efficiency by mitigating decreasing economies of scale in in-house innovation efforts. As a result, firms become more likely to outsource innovation efforts as they become more innovative, whereas the prevalence of offshoring depends on its associated trade costs.
Keywords: F14; F15; F23; O31; O32; 330; International integration; Service trade; Firm innovation